2011
DOI: 10.1007/s10765-011-1136-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transient Heat Conduction in a Hollow Sphere Using Duhamel Theorem

Abstract: In this article, analytical modeling of two-dimensional heat conduction in a hollow sphere is presented. The hollow sphere is subjected to time-dependent periodic boundary conditions at the inner and outer surfaces. The Duhamel theorem is employed to solve the problem where the periodic and time-dependent terms in the boundary conditions are considered. In the analysis, the thermophysical properties of the material are assumed to be isotropic and homogenous. Moreover, the effects of the temperature oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The traditional Fourier law implies an unbounded pace for thermal disturbance propagation [1] , [2] , which disagrees with some experimental observations [3] , [4] , [5] . In this model, any thermal disturbance imposed on a medium is instantly perceived through the entire body [6] , [7] .…”
Section: Introductionmentioning
confidence: 59%
“…The traditional Fourier law implies an unbounded pace for thermal disturbance propagation [1] , [2] , which disagrees with some experimental observations [3] , [4] , [5] . In this model, any thermal disturbance imposed on a medium is instantly perceived through the entire body [6] , [7] .…”
Section: Introductionmentioning
confidence: 59%
“…Based on the basic assumption, the heat dissipation problem of surrounding rock along the axis is simplified [8]. According to the law of conservation of energy and Fourier law, the integral equation of unsteady heat conduction in the temperature field of roadway surrounding rock is established as [13]…”
Section: Differential Equation Of Unsteady Heat Conduction Ofmentioning
confidence: 99%
“…In recent years, finite element method and finite volume method are also used to simulate the temperature field of roadway surrounding rock [8,9]. With the wide application of numerical calculation methods, the distribution of temperature field [10,11], the analysis of influencing factors [12,13], and the characteristics of heat and moisture exchange [14][15][16] are analyzed. In the site investigation and experimental testing, similar experimental platform for temperature field of roadway surrounding rock was established, and the unsteady state process of temperature field of roadway surrounding rock was analyzed [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with site investigation method, finite element method and finite difference method are more commonly used to study the temperature field in the roadway rock mass. More research results were found by the numerical calculation method concerning the rock mass temperature field prediction [3,11], influence factors of temperature distribution in the rock mass [12][13][14][15], and the disturbed domain of the temperature in the surrounding rock mass [16]. Most of the existing researches on the rock mass temperature distribution of the roadway, however, were not validated in laboratory.…”
Section: Introductionmentioning
confidence: 99%